Enhancing Competitiveness of Classification Bodies through OGS Digital Governance and Technological Development Challenges - Wibowo, Aprianto Hani; Sakapurnama, Eko (GoAcademica Research & Publishing, 2024)
This research assesses PT's OGS digital governance system, aiming to address its performance, technology development obstacles, and pursuit of IACS membership recognition. Objectives involve analyzing OGS performance, identifying development challenges, and proposing policy recommendations aligned with the